1990
DOI: 10.1007/bf00405106
|View full text |Cite
|
Sign up to set email alerts
|

Traditional plant treatments for diabetes. Studies in normal and streptozotocin diabetic mice

Abstract: The effects on glucose homeostasis of eleven plants used as traditional treatments for diabetes mellitus were evaluated in normal and streptozotocin diabetic mice. Dried leaves of agrimony (Agrimonia eupatoria), alfalfa (Medicago sativa), blackberry (Rubus fructicosus), celandine (Chelidonium majus), eucalyptus (Eucalyptus globulus), lady's mantle (Alchemilla vulgaris), and lily of the valley (Convallaria majalis); seeds of coriander (Coriandrum sativum); dried berries of juniper (Juniperus communis); bulbs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
245
1
4

Year Published

1997
1997
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(292 citation statements)
references
References 6 publications
25
245
1
4
Order By: Relevance
“…Figure 5 demonstrates the level of changes in body weight of experimental rats at before and after treatment. Weight loss is one of the major syndrome associated with diabetes, probably due to muscle wasting [37]. In our study the diabetic-induced rat group (Group II) showed significant weight loss (Fig.…”
Section: The Antidiabetic Activity Of Phytosynthesized Agnpssupporting
confidence: 51%
“…Figure 5 demonstrates the level of changes in body weight of experimental rats at before and after treatment. Weight loss is one of the major syndrome associated with diabetes, probably due to muscle wasting [37]. In our study the diabetic-induced rat group (Group II) showed significant weight loss (Fig.…”
Section: The Antidiabetic Activity Of Phytosynthesized Agnpssupporting
confidence: 51%
“…Normal healthy animals were found to be stable in their body weight whereas diabetic animals showed reduction in body weight. The decrease in weight in diabetes was due to the increased muscle wasting and loss of tissue proteins [27][28][29] . In the study, the reduction of body weight was diminished by extracts treatment after 21 days of treatment in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Different parts of the plant, including the fruits and the green herbs, are used for medicinal purposes such as dyspeptic complaints and loss of appetite (Blumenthal et al 2000). Pharmacological studies in animals have shown that coriander has anti-diabetic (Swanston-Flatt et al 1990;Gray and Flatt 1999), hypolipidemic, (Chithra and Leelamma 1997; and anti-cancer effects (Chithra and Leelamma 2000). Sedative-hypnotic activity of coriander seeds have been evaluated in scientific studies in mice (Emamghoreishi et al 2005).…”
Section: Introductionmentioning
confidence: 99%